2002
DOI: 10.1046/j.1525-1594.2002.07135.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes of the Arterial Systems in the Kidney under Prolonged Continuous Flow Left Heart Bypass

Abstract: We investigated morphological changes of the arterial systems in the kidneys under prolonged continuous flow left heart bypass. Twelve goats were subjected to 2 weeks of pulsatile left heart bypass followed by 4 weeks of continuous flow left heart bypass (group CF). After autopsy, the kidneys underwent pathological evaluation. Six normal healthy goats were used as controls. The media of the afferent arterioles of group CF were frequently thickened by an increase in the number of the mature smooth muscle cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Implantation of continuous-flow LVADs into animals demonstrate stable renal function for periods as long as 340 days postimplantation but there is also evidence of renal arterial smooth muscle cell hyperplasia, peri-arterial inflammatory cell infiltration, and interstitial nephritis (36)(37)(38)(39)(40). In one study, plasma renin activity increased significantly after LVAD insertion, possibly as an adaptive response to a lack of pulse pressure (39).…”
Section: Continuous Blood Flow and Renal Functionmentioning
confidence: 98%
“…Implantation of continuous-flow LVADs into animals demonstrate stable renal function for periods as long as 340 days postimplantation but there is also evidence of renal arterial smooth muscle cell hyperplasia, peri-arterial inflammatory cell infiltration, and interstitial nephritis (36)(37)(38)(39)(40). In one study, plasma renin activity increased significantly after LVAD insertion, possibly as an adaptive response to a lack of pulse pressure (39).…”
Section: Continuous Blood Flow and Renal Functionmentioning
confidence: 98%
“…The effect of LVAD therapy on kidney function and physiology has been studied recently with conflicting results and without a clear pathophysiological understanding [11,12,13,14,15,16,17,18,19]. One current limitation to studying this pathophysiology is that LVAD implantation trends have changed from historically pulsatile to exclusively continuous flow device types.…”
Section: What Effect Does Lvad Physiology Have On Kidney Function?mentioning
confidence: 99%
“…Further complicating this issue are animal studies showing that subjects implanted with CF-LVADs with intact LV function experienced negative renal effects, including renal arterial smooth muscle hyperplasia, inflammatory infiltration of the periarterial areas, and development of interstitial nephritis [13,14,15]. Recent studies focusing on homogeneous CF-LVAD populations have shown an initial improvement in kidney function in patients with both baseline normal eGFR and baseline impaired eGFR, followed by a slow decline in renal function over 6-12 months after device implantation [22,32].…”
Section: What Effect Does Lvad Physiology Have On Kidney Function?mentioning
confidence: 99%
“…Animal studies report proliferation of SMCs in the afferent arteriole in the renal cortex [93, 94] and perivascular tissue [94], but could not determine whether this change in morphology affected afferent arteriolar constriction and renal function. Infiltration of inflammatory cells in the renal cortical matrix has been observed, suggesting an immunologic mechanism for SMC hypertrophy [93].…”
Section: Renal Function In the Long Runmentioning
confidence: 99%